Motility as a morphogenic character in the genus Arthrobacter. - Stanlake, G J (1976)
Motility in Arthrobacter atrocyaneus, A. citreus, and A. simplex was found to correlate with the morphogenic cycle of these organisms. The percentage of the A. atrocyaneus and A. simplex populations that were flagellated at a given time during the growth cycle differed significantly from that of the normorphogenic Pseudomonas aeruginosa population. Flagellation in A. atrocyaneus was shown to be dependent upon the morphogenic cycle rather than upon growth. The commitment to flagellar synthesis in A. atrocyaneus was found to occur only after induction to the rod morphology. Flagellar synthesis in A. atrocyaneus was shown to be restricted to only a small segment of the morphogenic cycle.